Effect of Pharmacological Interventions on the Fronto-Cingulo-Parietal Cognitive Control Network in Psychiatric Disorders: A Transdiagnostic Systematic Review of fMRI Studies - van Amelsvoort, Thérèse; Hernaus, Dennis (Frontiers in Psychiatry, 2016)
Executive function deficits such as working memory, decision-making, and attention problems are a common feature of several psychiatric disorders for which no satisfactory treatment exists. Here, we transdiagnostically investigate the effects of pharmacological interventions (other than methylphenidate) on the fronto-cingulo-parietal cognitive control network, in order to identify functional brain markers for future pro-cognitive pharmacological interventions. 29 manuscripts investigated the effect of pharmacological treatment on executive function-related brain correlates in psychotic disorders (n=11), depression (n=4), bipolar disorder (n=4), ADHD (n=4), OCD (n=2), smoking dependence (n=2), alcohol dependence (n=1) and pathological gambling (n=1). In terms of impact on the fronto-cingulo-parietal networks, the preliminary evidence for catechol-o-methyl-transferase inhibitors, nicotinic receptor agonists and atomoxetine suggested was relatively consistent, the data for atypical antipsychotics and anticonvulsants moderate, and interpretation of the data for antidepressants was hampered by the employed study designs. Increased activity in task-relevant areas and decreased activity in task-irrelevant areas were the most common transdiagnostic effects of pharmacological treatment. These markers showed good positive and moderate negative predictive value. It is concluded that fronto-cingulo-parietal activity changes can serve as a marker for future pro-cognitive interventions. Future recommendations include the use of randomized double-blind designs and selective cholinergic and glutamatergic compounds.